Relationship of Substance P with the Degree of Atopic Dermatitis Severity - Paramita DA; Nasution K; Lubis NZ (Dove Medical Press, 2021)
Deryne Anggia Paramita, Khairina Nasution, Nova Zairina Lubis Department of Dermatology and Venereology, Faculty of Medicine, Universitas of Sumatera Utara, Sumatera Utara, 20155, IndonesiaCorrespondence: Deryne Anggia Paramita Email deryne.anggia@usu.ac.idIntroduction: Atopic dermatitis (AD) is a chronic inflammatory skin disease that starts during childhood with a varied course. Itching or incessant itching in severe cases, sleep disturbance, and infection-prone skin are the typical symptoms of this disease. Substance P is postulated to have an important role in AD. Increasing levels of substance P in AD induce the release of IFN-γ, IL-4, tumor necrosis factor-α (TNF-α), and IL-10 from peripheral blood mononuclear leukocytes, inducing an itching response.Methods: This study is a cross-sectional study that aims to analyze the relationship between serum substance P levels and AD severity in children using Score of AD (SCORAD), and to determine the mean serum substance P levels and severity of AD in patients with AD. This study also aims to find out the correlation of substance P levels with the SCORAD values.Results: Forty-six children (29 males; 17 females) with a mean age of 10.35 years (standard deviation (SD) = 4.01) were diagnosed with AD. The SCORAD index assessment was conducted to analyze AD (mean value, 23.15; SD = 9.42), and mild AD obtained the highest degree. The level of substance P was also examined (mean value, 300.88; SD = 127.55).Discussion: This study did not find a significant relationship between substance P levels and AD severity (p-value = 0.880), and there was no significant correlation between substance P levels and SCORAD values (p-value = 0.233; r = − 0.179). The limitations of this study include a small number of cases, no control group, and we only found two cases of severe AD. To generalize the results, further studies with wide range population and AD severity might be done in the future.Keywords: atopic dermatitis, SCORAD, substance P, pruritus